2021
DOI: 10.3389/fped.2021.611136
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Italian Adolescents During Covid-19 Outbreak

Abstract: Coronavirus disease 2019 (COVID-19) outbreak represented an experience of social isolation potentially leading to changes in the health quality of life. The aim of this study is to investigate the health-related quality of life during quarantine in early adolescents. Data were collected from 1,289 adolescents (mean age, 12.5; male, 622), at the beginning of the school year (September 2019, Standard Condition, SC) as part of the AVATAR project and during Phase 1 of the Italian lockdown (mid-late April 2020) (CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 38 publications
(42 reference statements)
3
32
0
3
Order By: Relevance
“…Nine of 11 cross-sectional studies also indicated lower levels of wellbeing or life satisfaction, while two indicated no significant changes. Greater decreases in wellbeing or life satisfaction among girls as compared with boys were reported in three studies (Magson et al, 2021 ; Mastorci et al, 2021 ; Thorisdottir et al, 2021 ). In a qualitative study, young people in the UK attributed their feelings of frustration, anger, and disappointment to the constant change, uncertainly, and lack of control associated with the pandemic context (Scott et al, 2021 ).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Nine of 11 cross-sectional studies also indicated lower levels of wellbeing or life satisfaction, while two indicated no significant changes. Greater decreases in wellbeing or life satisfaction among girls as compared with boys were reported in three studies (Magson et al, 2021 ; Mastorci et al, 2021 ; Thorisdottir et al, 2021 ). In a qualitative study, young people in the UK attributed their feelings of frustration, anger, and disappointment to the constant change, uncertainly, and lack of control associated with the pandemic context (Scott et al, 2021 ).…”
Section: Resultsmentioning
confidence: 87%
“…Of the 20 longitudinal studies, increased depressive symptoms during the pandemic were reported in 16 (Bignardi et al, 2020 ; Breaux et al, 2021 ; Buckner et al, 2021 ; Chen et al, 2021a , b ; Elmer et al, 2020 ; Evans et al, 2021 ; Giuntella et al, 2021 ; Hawes et al, 2021a , b ; Huckins et al, 2020 ; Hussong et al, 2021 ; Li et al, 2021a , b ; Magson et al, 2021 ; Yang et al, 2021 ; Zhang et al, 2020 ), no significant change in two (Janssen et al, 2020 ; Teng et al, 2021 ), and a reduction of depressive symptoms in two (Li et al, 2020 ; Xiang et al, 2020 ). Greater increases in mood disorder symptoms were reported among girls and young women as compared to their male counterparts in five studies (Elmer et al, 2020 ; Hawes et al, 2021a ; Magson et al, 2021 ; Mastorci et al, 2021 ; Thorisdottir et al, 2021 ). In contrast, in a study in Bangladesh, parents reported more emotional problems among girls than among boys before the pandemic, but prevalence reached near parity 3 months after the imposition of physical distancing measures in March 2020 (Mallik & Radwan, 2021 ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…On the other hand, regarding psychological well-being, the difference may be because girls are more worried about disease and may be more emotional, as previously reported in student studies [ 30 ] and have less ability to cope. Some previous findings have indicated that a sex effect emerged for physical and psychological well-being during the COVID-19 pandemic [ 31 ], whereas others did not find strong evidence [ 11 ]. Therefore, more studies should explore sex differences in the impact of the COVID-19 pandemic on HRQoL.…”
Section: Resultsmentioning
confidence: 99%